Outcomes with mismatched unrelated donor allogeneic hematopoietic stem cell transplantation in adults: A systematic review and meta-analysis - Mushtaq, Muhammad Umair; Shahzad, Moazzam; Tariq, Ezza; Iqbal, Qamar; Chaudhary, Sibgha Gull; Zafar, Muhammad U.; Anwar, Iqra; Ahmed, Nausheen; Bansal, Rajat; Singh, Anurag K.; Abhyankar, Sunil H.; Callander, Natalie S.; et al. (Frontiers in Oncology, 2022)
Background: Allogeneic hematopoietic stem cell transplantation (HSCT) is a potentially curative therapy for various hematologic disorders. Alternative donor strategies such as mismatched unrelated donors (MMUD) offer the option of HSCT to patients lacking a human leukocyte antigen (HLA)-matched donor. We conducted a systematic review and meta-analysis to evaluate outcomes after MMUD-HSCT. Methods: A literature search was performed on PubMed, Cochrane Library, and ClinicalTrials.gov from the inception date through April 6, 2022. After screening 2477 manuscripts, 19 studies were included. Data was extracted following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. Pooled analysis was done using the meta-package by Schwarzer et al. Proportions with 95% confidence intervals (CI) were computed. Results: A total of 3336 patients from 19 studies were included. The median age was 52.1 years, and 53% of recipients were males. The graft source was bone marrow in 19% and peripheral blood stem cells in 81% of recipients. The median time to transplant from hematologic diagnosis was 10 (1-247) months. Hematologic diagnoses included myeloid (82.9%), lymphoid (41.1%), and other disorders (3%). The reduced intensity and myeloablative conditioning were used in 65.6% and 32% of recipients, respectively. In-vivo T-cell depletion was performed in 56.7% of the patients. Most patients had one (87.9%) or two (11.4%) antigen HLA-mismatch. The pooled 1-year overall survival (OS) was 63.9% (95% CI 0.57-0.71, n=1426/2706), and the pooled 3-year OS was 42.1% (95% CI 0.34.2-0.50, n=907/2355). The pooled progression-free survival was 46.6% (95% CI 0.39-0.55, n=1295/3253) after a median follow-up of 1.8 (range 1-6) years. The pooled relapse rate was 26.8% (95% CI 0.22-0.32, n=972/3253) after a median follow-up of 2.25 (1-3) years. The pooled incidence of acute (grade II-IV) graft-versus-host disease (GVHD) and chronic GVHD was 36.4% (95% CI 0.31-0.42, n=1131/3030) and 41.2% (95% CI 0.35-0.48, n=1337/3228), respectively. The pooled non-relapse mortality was 22.6% (95% CI 0.17-0.29, n=888/3196) after a median follow-up of 2.6 (1-5) years. Conclusion: MMUD-HSCT has demonstrated favorable outcomes with an acceptable toxicity profile. It represents a promising option in patients lacking an HLA-matched or haploidentical donor and may expand HSCT access to underrepresented racial and ethnic populations.